Management of Atopic Eczema in primary care - Ainol Haniza Kherul Anuwar; Azura Mohd Affandi; Ch’ng Chin Chwen; Dawn Ambrose; Heah Sheau Szu; Khor Yek Huan; Lalitha Pillay a/p B. Gopinathan; Leow Wooi Leong; Mohd. Aminuddin Mohd. Yusof; Noor Zalmy Azizan; Sabeera Begum; Siti Shafatun Mohsin; et al. (Malaysian Family Physician, 2020)
Introduction: Atopic eczema (AE) is a common infammatory skin dermatosis that is increasing in prevalence. However, it can present in various clinical presentations, which leads to challenges in the diagnosis and treatment of the condition, especially in a primary care setting. Te Clinical Practice Guidelines on the Management of Atopic Eczema was developed by a multidisciplinary development group and approved by the Ministry of Health Malaysia in 2018. It covers the aspects of diagnosis, severity assessment, treatment, and referral